Effect of ethanol in mouthwashes on the surface hardness of a dental resin composite material - Indrani, Decky J.; Triaminingsih, S.; Nurvanita, N.; Andhesti, A.; Noviana, N. (Padjadjaran Journal of Dentistry, 2009)
The previous study has shown that dental resins exhibited changes in the surface hardness when soaked in alcoholic beverages. As ethanol was one of the components contained in some commercial mouthwashes, therefore, the present study aimed at the effect of ethanol in some mouthwashes on the surface hardness of a dental resin composite. Specimens were prepared from a light cured dental resin composite. The specimens were then immersed in some commercial mouthwashes for periods up to 14 days. The surface hardness of the specimens was then measured using a Microhardness tester. The results displayed reductions in surface hardness (p<0,01), upon one day of immersing the specimens in Bactidol®, Listerine® or Minosepe® mouthwash, respectively. The surface hardness curves from each mouthwash demonstrated a similar pattern which approached a plateau near 2 weeks. It can be concluded that the ethanol-containing mouthwashes appeared to have more implication on surface hardness of the dental resin composite and the effect of immersing in the mouthwashes was time-dependent; it decreased sharply on the first day of immersion, however, further changes, did not exist.